2015
DOI: 10.1177/1687814015573821
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of solid–liquidtwo-phase turbulent flow in Francis turbine runner with splitter bladesin sandy water

Abstract: As the key component of a hydroelectric power generation system, hydraulic turbine plays a decisive role in the overall performance of the system. There are many sandy rivers in the world, and turbines working in these rivers are seriously damaged. Therefore, the research of flow in sandy water has great theoretical significance and practical value. Based on the specific hydrological conditions of a hydropower station, the solid-liquid two-phase flow in the whole flow passage of a Francis turbine with splitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Generally, in the cavitating condition, water carries bubbles into the high regions of higher pressure, but in the case of cavitation-erosion, water, as well as sediment, carries the vapor bubbles into the high-pressure region [21]. For that reason, cavitation-erosion is more important than the normal cavitation condition.…”
Section: Cavitation-erosion Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in the cavitating condition, water carries bubbles into the high regions of higher pressure, but in the case of cavitation-erosion, water, as well as sediment, carries the vapor bubbles into the high-pressure region [21]. For that reason, cavitation-erosion is more important than the normal cavitation condition.…”
Section: Cavitation-erosion Effectsmentioning
confidence: 99%
“…Weili et al [20] investigated the cavitation characteristics due to the abrasion of the axial turbine in sand-laden water, and they found that cavitation was more likely to occur there than in clean water. On the other hand, Hong et al [21] numerically investigated solid-liquid flow behavior in the Francis turbine at different working load conditions. Rakibuzzaman et al [22] numerically and experimentally studied the cavitation erosion phenomena in a multistage centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been used to simulate the solid-liquid twophase turbulent flow in the runner of Francis turbines used in Jinping II Hydropower Station on Yalong River in China, and has been proved reliable [18].…”
Section: Mathematical Modelmentioning
confidence: 99%